Three-dimensional reduced-graphene/MnO2 prepared by plasma treatment as high-performance supercapacitor electrodes. (6th June 2018) - Liu, Runru; Wen, Dongdong; Zhang, Xueyu; Wang, Dejun; Yang, Qiang; Yuan, Beilei; Lü, Wei
Abstract: In this work, three-Dimensional nitrogen-doped graphene/MnO2 (NG/MnO2 ) was prepared by plasma treatment, which provides a high specific surface area due to porous structure and exhibits enhanced supercapacitor performance. The advantage of NG/MnO2 electrode was obvious compared with reduced graphene oxide/MnO2 (RGO/MnO2 ) which was prepared by traditional hydrothermal method, such as improved electrochemical property and better cycling stability. The specific capacitance of NG/MnO2 at the scan rate of 5 mV s −1 (393 F g −1 ) is higher than that of RGO/MnO2 (260 F g −1 ). In addition, NG/MnO2 showed higher durability with 90.2% capacitance retention than that of RGO/MnO2 (82%) after 5000 cycles. Such cheap and high-performance supercapacitor electrodes are available by our feasible plasma treatment, which give promise in large-scale commercial energy storage devices.